2006
DOI: 10.1242/jcs.02719
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule analysis of cadherin-mediated cell-cell adhesion

Abstract: Cadherins are ubiquitous cell surface molecules that are expressed in virtually all solid tissues and localize at sites of cell-cell contact. Cadherins form a large and diverse family of adhesion molecules, which play a crucial role in a multitude of cellular processes, including cell-cell adhesion, motility, and cell sorting in maturing organs and tissues, presumably because of their different binding capacity and specificity. Here, we develop a method that probes the biochemical and biophysical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
154
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(177 citation statements)
references
References 56 publications
23
154
0
Order By: Relevance
“…6). This observation is consistent with recent findings that the kinetics of weak E-CAD12 bonds differ Ϸ30-fold from C-CAD12 bonds (11) and that human N-CAD and canine E-CAD exhibit different mechanical properties (28). However, the modest absolute differences between the bond energies should result in a distribution of homophilic and heterophilic binding, as observed in the bead assays (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6). This observation is consistent with recent findings that the kinetics of weak E-CAD12 bonds differ Ϸ30-fold from C-CAD12 bonds (11) and that human N-CAD and canine E-CAD exhibit different mechanical properties (28). However, the modest absolute differences between the bond energies should result in a distribution of homophilic and heterophilic binding, as observed in the bead assays (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The order of homophilic adhesion is C͞C Ͼ E͞E Ͼ N͞N, in qualitative agreement with cell adhesion and single bond rupture measurements (11,12,20,(26)(27)(28).…”
Section: Discussionsupporting
confidence: 77%
“…This value is comparable with off rates determined for other cell adhesion molecules (E-cadherin [homotypic]: k off ϭ 1.01 s Ϫ1 ; Panorchan et al, 2006; and E-selectin/carbohydrate k off ϭ 0.72 s Ϫ1 ; Tees et al, 2001) but considerably higher than the off rate determined for integrin ␣ 5 ␤ 1 -fibronectin (k off ϭ 0.012-0.13 s Ϫ1 ; Li et al, 2003). Integrin adhesion must be dynamic so that cells can respond quickly to changes in external forces.…”
Section: Discussionsupporting
confidence: 84%
“…Epithelial cells typically express E-cadherin whereas mesenchymal cells express various other cadherins such as N-cadherin, R-cadherin, cadherin-7, or cadherin-11. Consistent with this, biophysical studies demonstrated that E-cadherin mediates stronger bonds at the molecular level than any other cadherins (Dufour et al, 1999;Chu et al, 2006;Panorchan et al, 2006). Moreover, although E-cadherin and N-cadherin may transiently coexist in certain cells, they are generally mutually exclusive, and studies on epithelial cell lines or in mouse and Xenopus embryos in which E-and N-cadherins have been interchanged clearly indicate that they can only partially substitute each other (Luo et al, 2001;Kan et al, 2007;Wheelock et al, 2008;Nandadasa et al, 2009;Libusova et al, 2010).…”
Section: Introductionmentioning
confidence: 90%